TINJAUAN PERBANDINGAN METODE PERHITUNGAN VOLUME TIMBUNAN DI PROYEK SIERRA INTERCULTURAL SCHOOL SECARA MANUAL DAN FOTOGRAMETRI - Silaban, Merdy Evalina; Prakasa, Muhammad Fajri Eka (LPPM Politeknik Astra, 2024)
The calculation of volume for earthwork is a critical aspect in various fields, including construction. This research aims to compare the methods of manual earthwork volume calculation and photogrammetry-based methods. The manual method relies on direct physical measurements on the earthwork, while photogrammetry involves processing aerial images taken from the air using aerial cameras or drones. This study presents an in-depth analysis of the accuracy, efficiency, and cost of both earthwork volume calculation methods. Additionally, environmental implications are explored to understand the environmental impacts of using each method. Given the significance of earthwork volume calculations in a project, research was conducted on the Sierra Intercultural School Project by comparing volumes using the manual method and photogrammetry-based method in AutoCAD Civil 3D, with calculations using Microsoft Excel as a comparative tool. The results were subsequently compared with the actual field earthwork volume. The research findings revealed a volume difference of Rp. 140,275,132 between the manual and photogrammetry-based methods, with a volume discrepancy of 838.75 cubic meters between the two methods. The results of the study indicate that the photogrammetry method can provide results comparable to the manual method in terms of accuracy but with greater time efficiency.